Epigenetic regulation in female reproduction: the impact of m6A on maternal-fetal health - Peipei Li; Yumeng Lin; Hongyun Ma; Jiao Zhang; Qiaorui Zhang; Ruihua Yan; Yang Fan (Cell Death Discovery)
Abstract With the development of public health, female diseases have become the focus of current concern. The unique reproductive anatomy of women leads to the development of gynecological diseases gradually become an important part of the socio-economic burden. Epigenetics plays an irreplaceable role in gynecologic diseases. As an important mRNA modification, m6A is involved in the maturation of ovum cells and maternal-fetal microenvironment. At present, researchers have found that m6A is involved in the regulation of gestational diabetes and other reproductive system diseases, but the specific mechanism is not clear. In this manuscript, we summarize the components of m6A, the biological function of m6A, the progression of m6A in the maternal-fetal microenvironment and a variety of gynecological diseases as well as the progression of targeted m6A treatment-related diseases, providing a new perspective for clinical treatment-related diseases.